Simulation on usage of water to an explosive compaction - Nor Azmaliana Binti Azmi (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is about the simulation on usage of water to an explosive compaction. The explosive compaction is a method to compress the metal powder into desired shape. Emulex is used as an explosive in this project. The main part in explosive compaction are dome, male compacter, female compacter, base and piston.